Low Testosterone in Adolescents & Young Adults - Cohen, Jordan; Nassau, Daniel E.; Patel, Premal; Ramasamy, Ranjith (Frontiers in Endocrinology, 2020)
Male hypogonadism, the clinical syndrome with variable symptoms associated with a low testosterone, can affect men of all ages. In older males, physiologic changes of the ageing testis, account for the majority of decreased testosterone levels in this population. For younger males and adolescents, the etiology of hypogonadism is commonly due to congenital or acquired conditions that disrupt the testis production of testosterone or signaling from the hypothalamic-pituitary-gonadal axis. Diagnosis of hypogonadism in younger males can be a challenge, as symptoms such as decreased libido or erectile dysfunction, common in the older men, are not usually present, and young men instead commonly complain of low-energy. While an underlying congenital cause should always be considered in young men with hypogonadism, acquired conditions such as obesity, diabetes, anabolic steroid or illicit drug use have all been associated with low testosterone levels. Outside of modifying identifiable risk factors for hypogonadism, pharmacologic testosterone therapy can also lead to therapeutic dilemmas in young men who desire paternity. Topical or injectable administration of testosterone, through negative feedback on the hypothalamus and pituitary, can decrease spermatogenesis, posing an infertility risk. Other agents that can replace testosterone or increase the body’s natural production of testosterone without decreasing spermatogenesis are preferred, such as intranasal testosterone, selective estrogen modulators, aromatase inhibitors or human-chorionic gonadotrophin, often used in combination. Clinicians must maintain a high level of suspicion to properly diagnose young men with hypogonadism and tailor treatment based on both the underlying etiology and fertility goals.